Preventive measures reduce exposure to polycyclic aromatic hydrocarbons at a graphite electrode plant. Issue 6 (June 1998) - dell'Omo, M; Muzi, G; Marchionna, G; Latini, L; Carrieri, P; Paolemili, P; Abbritti, G
Abstract : OBJECTIVE: This study assessed the efficacy of preventive measures in a graphite electrode plant aimed at reducing occupational exposure to polycyclic aromatic hydrocarbons (PAHs). METHODS: Electrode workers (n = 146) answered a questionnaire and provided an end of shift urine sample. Urinary 1-hydroxypyrene (1-hpur), a biological marker of exposure to PAHs, was measured by high performance liquid chromatography coupled with: (a) fluorescence detection. 1-Hydroxypyrene concentrations were compared with the concentrations measured before implementing the preventive measures; and (b) those of a control group of 54 men not occupationally exposed to PAHs. RESULTS: After implementation of preventive measures, median concentrations 1-hpur were significantly reduced in some groups of workers: by -24%, -37% and -30% in workers at the green electrode unit, one baking impregnation unit, and the laboratory, respectively. In workers at a second baking impregnation unit, in end product finishing and in the power station 1-hpur concentrations were unchanged. Urinary 1-hp concentrations were still significantly higher in each group of workers than in the control group (p < 0.001 for any comparison). Concentrations in the workers varied with the type of job, the highest values being found in workers engaged in the power station, in the two baking impregnation units and in the green electrode unit. CONCLUSIONS: Implementing preventive measures significantly reduced exposure to PAHs at a graphite electrode plant. The reduction in median and peak concentrations of 1-hpur, which reflects total exposure to, and internal dose of PAHs, was most evident in workers employed in the units where preventive measures had been taken. Despite an overall reduction, further preventive measures are needed to minimise exposure to PAHs and consequently the risk of adverse health effects.